1999
DOI: 10.1542/peds.104.6.1345
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Chronic Lung Disease in the Surfactant Era: A North Carolina Population-based Study of Very Low Birth Weight Infants

Abstract: This analysis suggests that with widespread use of surfactant, nosocomial infection, PDA, and water balance persist as risk factors for CLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
167
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(185 citation statements)
references
References 36 publications
11
167
1
6
Order By: Relevance
“…4,7,11,12 However, other observational studies have shown no difference in the early fluid regimens (first 4 to 14 days) of infants who develop BPD 27 or PDA 16,17 compared to those who do not.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…4,7,11,12 However, other observational studies have shown no difference in the early fluid regimens (first 4 to 14 days) of infants who develop BPD 27 or PDA 16,17 compared to those who do not.…”
Section: Discussionmentioning
confidence: 98%
“…Although over-hydration has been implicated in the development of both BPD and PDA, [1][2][3][4][5][6][7][8][9][10][11][12] it is not clear from prior studies whether complications arising from excessive hydration are due to fluid therapy itself, to an increase in total body water resulting from decreased renal losses or an increase in extracellular water volume due to third spacing. 6 To address this question, regression models were run that included weight change in grams per kg of body weight per day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A PDA is associated with serious neonatal morbidities, including necrotizing enterocolitis (NEC) 1 and chronic lung disease (CLD). 2,3 Although a cause and effect relationship between a PDA and these morbidities has not been established, many neonatologists administer indomethacin prophylactically to prevent intraventricular hemorrhage (IVH), with the additional benefit of reducing the incidence of a symptomatic PDA. 4 Indomethacin treatment is also used beyond the first day of life (DOL) to effect closure of PDAs that are either identified on echocardiogram or by physical examination, particularly those that are associated with signs and symptoms (i.e.…”
Section: Introductionmentioning
confidence: 99%